Developing a digital platform literacy framework - Seungyeon Ha; Seongcheol Kim (International Telecommunications Society (ITS), 2023)
This article introduces the innovative concept of platform literacy, specifically within the context of digital platforms. In today's digital economy, where digital platforms serve as essential tools in people's lives and form the core of the digital ecosystem, the ability to effectively utilize these platforms becomes crucial. This study systematically examines existing literature on digital platforms and digital literacy to establish a conceptual foundation for assessing an individual's platform literacy. Drawing upon insights from the digital literacy framework, we propose a platform literacy framework that can be applied in practical settings. Methodologically, we conducted an extensive review of 735 research papers on digital literacy to gather definitions and frameworks. As a result, we identified seven core constructs and three main proficiencies that constitute the platform literacy framework. Moreover, to adapt the framework to the various digital platform context, we categorized it into fixed attributes and variable attributes. This article contributes to the growing body of knowledge on digital literacy by offering a comprehensive framework for understanding platform literacy within the digital platform landscape.
Keywords: 330; platform literacy; digital literacy; digital platform; digital platform literacy framework